Ability emotional intelligence and life satisfaction: Positive and negative affect as mediators. (November 2016) - Extremera, Natalio; Rey, Lourdes
Abstract: The present study examined the link between ability emotional intelligence (EI), positive and negative affect, and life satisfaction in a relatively wide sample of 721 Spanish undergraduate students. Data were collected using the Mayer-Salovey-Caruso Emotional Intelligence Test, the Positive and Negative Affect Schedule, and the Satisfaction with Life Scale. Correlational results indicated that ability EI was significantly and positively associated with life satisfaction and positive affect, and inversely with negative affect. Thus, positive and negative affect were significantly associated with life satisfaction in the expected way. Importantly, path analyses indicated that both positive and negative affect played a fully mediating role in the link between EI and life satisfaction. These results add to the small but growing literature about EI, assessed by a performance-based measure, and well-being, and encourage further research about affective processes by which these emotional skills influence diverse well-being outcomes. Highlights: Emotional intelligence was associated with life satisfaction. Positive and negative affect were associated with life satisfaction. Positive and negative affect fully mediated the emotional intelligence–life satisfaction link.